Impact of Education Expansion on employment in Bangladesh Comparing Two Cases of Villages in Remote and Suburban Rural Settings [Sample] (Journal of International Cooperation in Education, 2016)
A number of institutions and organizations such as the government, NGO's, international development partners and agencies and religious groups have been working to develop education in Bangladesh, educational development projects related to the Education for All (EFA) have contributed to the development of the education sector. As a result, enrollment rates have increased significantly over the past two decades in Bangladesh, not only in primary schools but also, at the secondary level. As a result, it is increasingly common to find individuals with Secondary Certificate (SSC), Higher Secondary Certificate (HSC) and even higher education degrees in the population at large. Still, 85% of the population in Bangladesh lives in rural areas. At this point, the most important questions are whether educated rural people are able to find employment after graduation and whether educational development policies expand peoples's life options. This study compares education development in two regional settings, one in the western part of the country and the other in the east. The aim is understand educational attainment in two different geographical settings--one in remote rural area far from industry and the other a semi-urban rural area closer to industry.